Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia - Molano, Fredy; Morales, Irina; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2018)
Two new species of the salina group of the genus Rhagovelia Mayr, 1865 (Veliidae) from Colombia are described, illustrated, and included in an updated key. Rhagovelia nuqui sp. nov. is described from the Pacific Region of Colombia and Rhagovelia tintipan sp. nov., is described from the Caribbean Region of the country. The new species are diagnosed by body length and conditions of the male hind femoral spines, paramere shape, and antenna and fore femur color. Additionally, R. colombiana (Polhemus & Manzano, 1992) is redescribed and its range is extended to Chocó departament. Finally, R. plumbea Uhler, 1894 is recorded for the first time from Colombia.